Socialization of Calculating Income Tax with The Method of Calculation of Net Income for MSMEs in Kembangan Selatan Village, West Jakarta - Sormin, Feber; Kurniawati , Elok (EQUATOR SINAR AKADEMIA, 2025)
The purpose of the PkM activity is to increase understanding of the calculation of PPh payable, and minimize tax risks for WPOP UMKM.Problems: 1). Many WPOP UMKM are not aware that the tariff incentive for certain businesses with 0.5% has ended. 2). Many WPOP do not understand that if the use of Final PPh ends, it must be continued with the normal rate based on the calculation of NPPN. 3). Maintain the sustainability of MSME businesses from the imposition of tax sanctions due to a lack of understanding of the regulations.Solution: With the counseling method through presentations, questions and answers, demonstrations through practitioners who explain about Tax regulations, it is hoped that it can be a solution: 1). Increase the understanding of WPOP UMKM regarding the calculation of PPh which is their obligation, and 2). provide knowledge about calculating DPP with the NPPN method for WPOP. 3). Provide understanding through examples of the process, how to calculate WPOP PPh. Activity Results: With the counseling method through presentations, questions and answers, demonstrations through direct presentation of material to WPOP UMKM PkM participants, it has become a solution: 1). Producing WPOP who know, understand the sustainability of how to calculate the Taxable Basis (DPP) with the NPPN method in calculating the PPh WPOP UMKM. 2). WPOP UMKM avoids the risk of errors in applying PPh calculations, 3). WPOP UMKM is more obedient in implementing the Rights and obligations of Taxpayers. 4). Providing input contributions to the government, academics, and other parties.